The impact of climate change on seasonal thawing and water regime of soils in the permafrost zone - Sergey A. Lavrov (Water sector of Russia problems technologies management, 2022)
It is impossible to explain impact of climate change on the surface and underground runoff of the permafrost zone without studying the seasonal processes of thawing of permafrost soils. These processes directly affect infiltration, evaporation and other hydro/physical characteristics, that is, they almost completely determine the mechanisms of runoff formation and its climatic interdependence.